ORIENTATION TO FREEDOM AND POWER OF AMBITIOUS PERSON IN EARLY ADOLESCENCE - Barsukova, Oksana (Journal of process management and new technologies, 2020)
The article presents the results of an empirical study of orientation to power and freedom of ambitious person. Ambition, orientation to power and freedom are understood as motives of a person’s social activity. People who consider themselves ambitious have a medium (53.33%) and high (46.66%) orientation to freedom, a low (60.00%) and medium (40.00%) orientation to power.